Evaluasi Efektivitas Layanan Pada Jalan Tol Balikpapan-Samarinda Dalam Memenuhi Kepuasan Pengguna - Zsagheta Ihwal Rezky; Apif Miptahul Hajji; Henri Siswanto (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The construction of toll roads is aimed at accelerating means of transportation, tourism and economic growth as well as shortening the travel time. In order to support the implementation of these objectives, a toll road minimum service standard has been established. This study aims to assess how effective the Balikpapan-Samarinda Toll Road service is in meeting user satisfaction. There are 30 service indicators for the Balikpapan-Samarinda Toll Road based on toll road minimum service standards that are measured to see the level of user satisfaction. The 30 service indicators represent the five dimensions of Servqual. The method used in measuring user satisfaction is the Customer Satisfaction Index (CSI) and Important Performance Analysis (IPA) and also SWOT analysis. The conclusions are (1) Based on the CSI method, the value of the service user satisfaction index is 74.11% which is included in the criteria of 'satisfied'. (2) Based on the IPA method, it shows that there are 7 service indicators included in Quadrant I, where the frequency of service indicators is not more than (1/4) 30 service indicators namely 8 indicators, indicating effective service in meeting user satisfaction. (3) Based on SWOT analysis produces a matrix that includes three SO strategies, two ST strategies, two WO strategies and three WT strategies , where the best strategy to apply is the WT strategy.